Association of Animal Protein Adequacy with Nutritional Status: A Study on High School Adolescents in Semarang City - Melati, Sekar; Ayuningtyas, Rr. Annisa; Jauharany, Firdananda Fikri; Ulvie, Yuliana Noor Setiawati (Jurnal Gizi dan Pangan, 2023)
This study aimed to determine the relationship between animal protein and calcium adequacy with nutritional status. This is a cross–sectional study with 78 subjects selected by purposive sampling method. This study was conducted in State Senior High School 2 and State Senior High School 9 Semarang. The data were analyzed using Spearman's rank test. The results showed an association between animal protein adequacy and nutritional status (p=0.027, r=-0.250). There was no association between calcium adequacy and nutritional status (p=0.574, r=0.065). In conclusion, protein adequacy is associated with nutritional status among adolescents, but calcium is not.